ANALISIS STANDAR KOMPETENSI KELULUSAN PENDIDIKAN DASAR - Risma Tri Nanda; Rohanda Has Ramadan; Sahrani Taskia; Rizki Ananda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the achievement of graduate competency standards through the understanding of Islamic Education (PAI) teachers and non-PAI teachers on each indicator. This type of research is descriptive qualitative research. The instrument used refers to seven indicators of graduate standards in the form of interview guidelines using a questionnaire. Data collection was carried out using Google Forms, which were distributed to 5 PAI teachers and 5 non-PAI teachers at the elementary school level. Authentic data collection and triangulation of interview results with several teachers on the lowest indicators were conducted, followed by an analysis of the comparison between PAI and non-PAI teachers. The results of this study indicate that the level of understanding of PAI teachers regarding the indicators of graduate competency standards is superior to that of non-PAI teachers. The achievement of graduate standard indicators has not fully reached its maximum potential, including the lack of workshops or seminars and the absence of literacy programs/training for students in schools. Keywords: education, graduate competency standards achievement, graduate competency standards indicators